Austria : 2007 Article IV Consultation-Staff Report; Staff Statement; Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director for Austria. (IMF Staff Country Reports; Country Report, 2007)
This 2007 Article IV Consultation highlights that the favorable economic outcome for Austria is owed to a combination of stability-oriented macropolicies, a range of structural reforms, strong international competitiveness resulting from a social partnership that facilitates wage moderation, and an orientation toward fast-growing economies in Central, Eastern, and Southeastern Europe (CESE). The banking sector continues to do well overall. The authorities are taking action to further improve monitoring of the Austrian banks' activities in CESE, including foreign currency lending, and are also stepping up collaboration with host supervisors.